ANALYSIS OF CONSUMER PERCEPTIONS AND WILLINGNESS TO PAY AGAINST LOCAL AND IMPORT FRUITS IN MEDAN CASE STUDY ORANGE AND APPLE - Hadriman Khair (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
This study was aim to to analyze Consumer perception in Medan against local and import fruits as well as any factors affecting consumer products to purchase local and import fruits. Some 350 respondents were interviewed using a questionnaire. The data is obtained has been analyzed using descriptive analysis, perception analysis, factor analysis and test data quality. The descriptive analysis shows that the majority of respondents were aged 17-24 years, male 72,9%, college students and recent high school education 93,4 %. In the analysis of the perception there are 350 respondents who answered the questionnaire returns and then there were 263 respondents to know when to ask Do you know about the local fruits on the market, while 87 respondents have heard and know little. Ther are 350 respondents who answered the questionnaire returns and there were 186 respondents who answered knew when asked Do you know about fruit imports in the market. The remaining 162 respondents had heard of but knew little and 2 respondents claimed not to know. For the factor analysis KMO test value obtained for 0.746 (great for the meticulous sampling), commonality 0.384 to 0.770 and total variance is 46,986 percent. In the quality test data on the reliability of the test can be of value for Cronbach's Alpha based on standardized items 0.782 is greater than the basic standard Cronbach's Alpha 0.756 which can be deduced that the grains realibel questions.Keywords: Perception, Local, Import, Fruit, Medan